2020
DOI: 10.1186/s13046-020-01569-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of circulating tumor DNA in primary colorectal cancer at surgery and during post-surgery follow-up by liquid biopsy

Abstract: Background: Liquid biopsy (LB) in early-stage, non-metastatic colorectal cancer (CRC) must be sensitive enough to detect extremely low circulating tumor DNA (ctDNA) levels. This challenge has been seldom and non-systematically investigated. Methods: Next generation sequencing (NGS) and digital PCR (dPCR) were combined to test tumor DNAs (tDNAs) and paired ctDNAs collected at surgery from 39 patients, 12 of whom were also monitored during the immediate post-surgery follow up. Patients treated for metastatic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…All DNA samples were then quantified by a Qubit Fluorometer (Termofisher Scientific, Waltham, Massachusetts, USA) using a Qubit® dsDNA HS Assay Kit. Library preparation was performed on 10 ng DNA by the Ion AmpliSeq Library Kit 2.0 (Termofisher Scientific) and the Colon and Lung Panel (Life Technologies) was used to sequencing the entire coding regions of TP53, as previously described [ 16 ]. Briefly, the prepared libraries were sequenced on Ion S5 Sequencer using an Ion 540 Chip and an Ion 540 kit–Chef (all Thermo Fisher Scientific) with configuration 500 flows covering the 200 bp library read length.…”
Section: Methodsmentioning
confidence: 99%
“…All DNA samples were then quantified by a Qubit Fluorometer (Termofisher Scientific, Waltham, Massachusetts, USA) using a Qubit® dsDNA HS Assay Kit. Library preparation was performed on 10 ng DNA by the Ion AmpliSeq Library Kit 2.0 (Termofisher Scientific) and the Colon and Lung Panel (Life Technologies) was used to sequencing the entire coding regions of TP53, as previously described [ 16 ]. Briefly, the prepared libraries were sequenced on Ion S5 Sequencer using an Ion 540 Chip and an Ion 540 kit–Chef (all Thermo Fisher Scientific) with configuration 500 flows covering the 200 bp library read length.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective analysis of the IDEA-France data also reported that the detection of ctDNA postoperatively is an independent adverse prognostic marker for cancer recurrence (adjusted HR,1.85; p < 0.001) in stage III patients treated with oxaliplatin-based ACT [ 49 ]. A similar study by Allegretti et al [ 50 ] reported that persistence and absence of ctDNA at the time of first post-operative (3 month) follow-up were associated with fast relapse and a disease-free status in three and seven patients, respectively. In addition, this study reported improved sensitivity (58.8% to 63.6%) when ctDNA result was analyzed in combination with serum CEA level.…”
Section: Role Of Ctdna In the Detection Of Minimal Residual Diseasmentioning
confidence: 54%
“…Spiking experiments prompted us to apply the NESPRI assay to the direct detection of KRAS mutated ctDNA present in the blood of metastatic CRC patients. These specimens were preliminarily validated by NGS and digital PCR (dPCR) 28 , carried a unique RAS mutation per sample and displayed different variant allele frequencies (VAF, i.e., the percentage of mutated reads) and mutated copies per ml (Table 4). We applied the already described NESPRI assay operating under continuous flow conditions so that kinetic curves useful to check the correct outcome of each step of the assay were also recorded during the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Data here reported displays the clinical validity of the NESPRI assay and its ability to discriminate between normal and RAS mutated genotype into separate groups (CRC and control group). These were shown to be associated with different treatment indications and clinical outcomes 28 . The assay has been shown to exhibit analytical validity also in testing liquid biopsies from CRC patients.…”
Section: Resultsmentioning
confidence: 99%